Catalyzing the Translation of Patient-Centered Research Into United States Trauma Care Systems: A Case Example. (August 2021) - Zatzick, Douglas; Moloney, Kathleen; Palinkas, Lawrence; Thomas, Peter; Anderson, Kristina; Whiteside, Lauren; Nehra, Deepika; Bulger, Eileen
Abstract : Background: The expedient translation of research findings into sustainable intervention procedures is a longstanding health care system priority. The Patient-Centered Outcomes Research Institute (PCORI) has facilitated the development of "research done differently, " with a central tenet that key stakeholders can be productively engaged throughout the research process. Literature review revealed few examples of whether, as originally posited, PCORI's innovative stakeholder-driven approach could catalyze the expedient translation of research results into practice. Objectives: This narrative review traces the historical development of an American College of Surgeons Committee on Trauma (ACS/COT) policy guidance, facilitated by evidence supplied by the PCORI-funded studies evaluating the delivery of patient-centered care transitions. Key elements catalyzing the guidance are reviewed, including the sustained engagement of ACS/COT policy stakeholders who have the capacity to invoke system-level implementation strategies, such as regulatory mandates linked to verification site visits. Other key elements, including the encouragement of patient stakeholder voice in policy decisions and the incorporation of end-of-study policy summits in pragmatic comparative effectiveness trial design, are discussed. Conclusions: Informed by comparative effectiveness trials, ACS/COT policy has expedited introduction of the patient-centered care construct into US trauma care systems. A comparative health care systems conceptual framework for transitional care which incorporates Research Lifecycle, pragmatic clinical trial and implementation science models is articulated. When combined with Rapid Assessment Procedure Informed Clinical Ethnography (RAPICE), employed as a targeted implementation strategy, this approach may accelerate the sustainable delivery of high-quality patient-centered care transitions for US trauma care systems.